The Influence of Perceived Ease of Use, Security, and Trust on Generation Z's Decision to Use Bank Jago - Salsabila Anggraeni; Muttaqin, Aminnullah Achmad (Contemporary Studies in Economic, Finance and Banking, 2025)
The rapid growth of digital banking in Indonesia has reached Rp15.881.5 trillion in transactions during the first quarter of 2024, with Generation Z representing 60% of digital bank users. This study aims to analyze the influence of perceived ease of use, security, and trust on Generation Z's decision to use Bank Jago digital banking services. Using a quantitative approach with descriptive-explanatory design, data were collected from 130 Generation Z respondents who actively use Bank Jago services through online surveys. Principal Component Regression Analysis (PCRA) was employed to examine the relationships between variables. The results demonstrate that all three factors (perceived ease of use, security, and trust) positively and significantly influence Generation Z's decision to use Bank Jago services (t-value = 11.992, p < 0.001). Among these variables, perceived ease of use emerged as the strongest predictor, indicating that Generation Z prioritizes user-friendly interfaces and seamless digital experiences. The findings provide valuable insights for digital banking institutions to develop targeted strategies focusing on intuitive design while maintaining robust security measures to attract and retain.